The Relationship Between the Cultural Practice of Abstinence During Pregnancy and the Incidence of Preeclampsia in the Working Area of the Tamanan Public Health Center, Bondowoso - Rifah, Muttimatur; Azza, Awatiful; Kholifah, Siti (D'Nursing and Health Journal (DNHJ), 2022)
Introduction: The culture of abstinence is a habit or belief of the community that prohibits pregnant women from consuming certain types of food. Mothers tend not to consume sea fish, shrimp, and eggs which can cause pregnant women to experience malnutrition which increases the risk of preeclampsia. Method: This study uses quantitative research with a correlation design and uses a cross-sectional approach. Conducted on 134 population of pregnant women with 100 samples. Collecting data by questionnaires and study of documents through the MCH handbook. Analysis using Spearman Rho statistic at p-value <0.05. Result: The results of this study indicate a p-value of 0.000 with an R-value of 0.621. There is a relationship between cultural practices of abstinence during pregnancy and the incidence of preeclampsia. Conclusion: The practice of abstinence from eating is still widely practiced in rural communities. This condition can be a risk factor for preeclampsia in pregnant women.